A CROSS-SECTIONAL SCREENING SURVEY ON THE SEROPREVALENCE OF HEPATITIS B AND HEPATITIS C AMONGST THE GENERAL POPULATION OF RURAL DISTRICTS OF SINDH, PAKISTAN - ASGHAR,Muhammad Sohaib (2021)
ABSTRACT BACKGROUND: Viral hepatitis is a global phenomenon, with the disease burden varying on a daily basis. Amongst chronic infections, hepatitis B virus and hepatitis C virus (HCV) are egregiously linked to severe health-related complications, with a worldwide prevalence of 248 million and 71 million respectively. Amongst the developing world, a hand full of countries are exhibiting a gross decline in chronic viral infection prevalence, like Bangladesh. While countries such as India have a consistent prevalence, Pakistan bears one of the largest proportions of chronic viral hepatitis globally with increasing trends shown year-by-year. Various old literature texts have stated an approximate national prevalence rate around 2.6% and 5.3% of hepatitis B and C respectively. OBJECTIVE: The objective of this study was to determine the current seroprevalence rates of chronic viral hepatitis amongst the general population of rural Sindh using a screening program to determine the current disease burden. METHODS: An observational, cross-sectional survey based on a screening program was conducted in 5 districts with a combined population of over 6.5 million. The screening was carried out via the administration of various camps with the assistance of local social workers and welfare organizations. A total of 24,322 individuals met the inclusion criteria and were screened through (HBsAg/HCV) rapid test cassette (WC) Imu-Med one-step diagnostic test. RESULTS: Hepatitis B was found positive in 964 (3.96%) individuals including 421 (43.67%) males and 543 (56.32%) females, while hepatitis C was positive in 2872 (11.80%) individuals including 1474 (51.32%) males and 1398 (48.67%) females. The prevalence amongst the districts varied between 0.97% and 9.06% for hepatitis B, and 1.61% and 29.50% for hepatitis C, respectively. Umerkot was found to be the most prevalent district amongst rural Sindh, while Badin had the least number of seropositive people. The second most prevalent district of the study population was found to be Tando Allahyar followed by Mirpur Khas. The combined seroprevalence of 15.76% was calculated for hepatitis B and C together amongst the five studied districts of rural and peri-urban Sindh. CONCLUSION: The alarmingly high prevalence rates revealed in our study warrant the urgent need to generate multiple effective strategies in the region to enhance awareness amongst the general population regarding screening, prevention, and prompt treatment of the disease.